Design of optical-electronic sensor for ablation of spacecraft heat protection - Hornostaev, G.; Pasichny, V.; Lytvynenko, Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Results of designing and studying the characteristics of the fiber-optic sensor for the ablation of the low-sublimating heat protection which intended for the use on the being got down module of article “Mars-5” are represented. The originality of development consists of guarantee for continuous measurement of the instantaneous value of thickness of heat protective coating of the article during its descent. Achieving this goal is ensured by the application of two light-guide sensors, one of which is made from color glass-light filter.